Empathy and Dyspathy with Androids: Philosophical, Fictional, and (Neuro)Psychological Perspectives (Konturen, 2010)
The fact that we develop feelings towards androids, i.e., objects with a humanlike appearance, has fascinated people since ancient times. However, as a short survey of the topic in history, science fiction literature and film shows, our emotional reactions towards them are ambivalent. On the one hand, we can develop feelings of empathy almost as we do with real human beings; on the other hand, we feel repulsion or dyspathy when those creatures show a very high degree of human likeness. Recently, Japanese roboticist Masahiro Mori coined the term “uncanny valley” to refer to this effect. The aim of this essay is, first, to give an explanation as to why we feel empathy towards androids although we know that they do not have feelings themselves. This presupposes a perception-based concept of empathy which is going to be developed on the basis of some of Theodor Lipps’ ideas. The second question to be answered is why empathy with androids turns into dyspathy when they become very humanlike. As I will argue, this is due to a particular kind of interference between perception and the imagination when confronted with very humanlike objects. This makes androids quite special objects right at the divide between humans and non-humans. They are non-human, but we feel ill at ease when treating them as mere objects.